2013
DOI: 10.1007/s10495-013-0958-8
|View full text |Cite
|
Sign up to set email alerts
|

TAT-RasGAP317–326-mediated tumor cell death sensitization can occur independently of Bax and Bak

Abstract: The increase of cancer specificity and efficacy of anti-tumoral agents are prime strategies to overcome the deleterious side effects associated with anti-cancer treatments. We described earlier a cell-permeable protease-resistant peptide derived from the p120 RasGAP protein,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…10,11 Any modification in this sequence would lead to tumour growth. 10,11 Any modification in this sequence would lead to tumour growth.…”
Section: And References Therein)mentioning
confidence: 99%
“…10,11 Any modification in this sequence would lead to tumour growth. 10,11 Any modification in this sequence would lead to tumour growth.…”
Section: And References Therein)mentioning
confidence: 99%
“…Fragment N2 and fragment N2-derived peptides sensitize tumor cells to anti-cancer drugs (28, 64 -66), but the underlying mechanisms remain obscure (67,68). Here we show that fragment N2 potently inhibits FGF1-induced phosphorylation of ERK2 and Akt.…”
Section: Discussionmentioning
confidence: 67%
“…The mechanism of action of TAT-RasGAP 317-326 remains to be precisely determined [ 18 20 ]. We initially assumed that working with a large panel of cell lines and cytotoxic agents would allow us to draw a pattern that could be used to predict which type of childhood tumors display sensitivity to TAT-RasGAP 317-326 in response to a given drug.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that this peptide does not favor the death of tumor cells by modulating Ras activity, MAPK signaling pathways, NF-κB transcriptional activity, Akt protein levels and phosphorylation status [ 18 , 19 ]. Moreover, the Bcl-2 family members, which regulate mitochondrial-dependent cell death, were shown to be individually dispensable for the sensitizing activity of the peptide [ 20 ].…”
Section: Introductionmentioning
confidence: 99%